Continuous Positive Airway Pressure Adherence for Obstructive Sleep Apnea. (26th May 2011) - Somers, Melissa L.; Peterson, Ed; Sharma, Saurabh; Yaremchuk, Kathleen
Abstract : Objective. To determine predictors of patient adherence to CPAP. Design. A retrospective chart review identified patients with AHI values greater than 15 who were recommended to receive CPAP. Compliance was measured at a 1-to 4-month interval and at 1 year. Results. There were 106 of 368 (29%) patients who received CPAP therapy that were compliant with CPAP use at 1 to 4 months. Forty-six patients (12%) were using CPAP at one year. For the male group at one year, the model demonstrated the AHI value (P   value = .026 ) as a predictor of compliance if greater than 27.3 and a significant two-way interaction between age and AHI (P = .023 ). Increased length of time from the initial visit and receiving the CPAP machine was associated with poorer compliance (P = .002 ). Those living in areas with higher incomes and with a higher percentage of non-high-school graduates were more likely to be compliant (P = .01 andP = .044 ). Conclusion. Older male patients with higher AHI values were noted to be more adherent to CPAP. Efforts should be made to try to minimize the length of time between the initial visit and the time to receive CPAP to improve compliance.